New Cultural Histories of India : materiality and practices - Partha Chatterjee, Ed (New cultural histories of India, 2014)
Most of the papers presented at the conference on 'New Cultural Histories of India', organized by Centre for Studies in Social Sciences during 5-7 January 2010.